Dinitrogen fixation in aphotic oxygenated marine environments - Rahav, Eyal; Bar-Zeev, Edo; Ohayion, Sarah; Elifantz, Hila; Belkin, Natalia; Herut, Barak; Mulholland, Margaret R.; Berman-Frank, Ilana R. (Frontiers in Microbiology, 2013)
We measured N2 fixation rates from oceanic zones that have traditionally been ignored as sources of biological N2 fixation; the aphotic, fully oxygenated, nitrate (NO3-)-rich, waters of the oligotrophic Levantine Basin (LB) and the Gulf of Aqaba (GA). N2 fixation rates measured from pelagic aphotic waters to depths up to 720 m, during the mixed and stratified periods, ranged from 0.01 nmol N L-1 d-1 to 0.38 nmol N L-1 d-1. N2 fixation rates correlated significantly with bacterial productivity and heterotrophic diazotrophs were identified from aphotic as well as photic depths. Dissolved free amino acid amendments to whole water from the GA enhanced bacterial productivity by 2to 3.5 and N2 fixation rates by ~ 2 fold in samples collected from aphotic depths while in amendments to water from photic depths bacterial productivity increased 2 to 6 fold while N2 fixation rates increased by a factor of 2 to 4 illustrating that both BP an heterotrophic N2 fixation are carbon limited. Experimental manipulations of aphotic waters from the LB demonstrated a significant positive correlation between transparent exopolymeric particles (TEP) concentration and N2 fixation rates. This suggests that sinking organic material and high carbon (C): nitrogen (N) micro-environments (such as TEP-based aggregates or marine snow) could support high heterotrophic N2 fixation rates in oxygenated surface waters and in the aphotic zones. Indeed, our calculations show that aphotic N2 fixation accounted for 37 to 75 % of the total daily integrated N2 fixation rates at both locations in the Mediterranean and Red Seas with rates equal or greater to those measured from the photic layers. Moreover, our results indicate that that while N2 fixation may be limited in the surface waters, aphotic, pelagic N2 fixation may contribute significantly to new N inputs in other oligotrophic basins, yet it is currently not included in regional or global N budgets.